Effect of fly ash and ground waste glass as cement replacement in concrete 3D-Printing for sustainable construction - Samrani, Phebe; Cao, Yifang; Fimbres-Weihs, Gustavo; Sanjaya, Eric; Abbas, Ali (Frontiers in Built Environment, 2024)
Concrete 3D printing is a promising manufacturing technology for producing geometrically complex structures efficiently and cost-effectively, by eliminating the need for formwork, reducing labor, and minimizing waste. This method has the potential to lower carbon emissions and resource use. However, it does not mitigate the carbon emissions associated with cement production. Nonetheless, utilizing waste materials in concrete 3D printing may reduce concrete carbon emissions and support recycling. This study investigates the use of two industrial waste materials–fly ash (FA) and ground waste glass (GWG)–as partial substitutes for ordinary Portland Cement (PC) in 3D printable cement paste. The chemical composition, particle size distribution, rheological properties, and flexural strength of the mixtures were analyzed. Results show that specimens containing waste materials achieved strengths comparable to traditional cement mixtures. The flexural strength reduction in 3D printed versus cast specimens varied across mixtures: control (66% reduction), FA20 (35%), FA10-GWG10 (35%), GWG10 (32%), FA10 (11%), and GWG20 (4%). Hence, incorporating waste materials in concrete 3D printing is recommended, as it maintains mechanical integrity while promoting recycling and upcycling of industrial waste.